Q’FAST: Qada Fasting Mobile Application - Aziz, Ain; Saiful Faizal, Nur Aisyatul Balqis; Mahmod, Nurnabila; Roslan, Rosfuzah (Multidisciplinary Applied Research and Innovation, 2026)
‘Fasting’ during the month of Ramadan is a fundamental obligation in Islam. However, due to unavoidable circumstances such as illness, menstruation, travel, or pregnancy, Muslims may miss their fasts and are required to perform ‘qada fasting’ or pay ‘fidyah’. Many individuals face difficulties in tracking missed fasts and accurately calculating fidyah payments. To address this issue, the Q’FAST – Qada Fasting Mobile Application was developed to assist the Muslim community in managing their ‘fasting’ obligations more effectively. The application enables users to record missed and completed fasts, calculate fidyah based on official state rates in Malaysia, and access educational information related to ‘fasting’ practices. The system was developed using Flutter and Firebase, following the Waterfall methodology to ensure a structured development process. A usability evaluation was conducted using the UMUX (Usability Metric for User Experience) questionnaire involving 10 users. The results indicate high user satisfaction and system performance, with satisfaction and efficiency achieving 98%, while effectiveness and ease of use recorded 96%. These findings demonstrate that the application is user-friendly, efficient, and capable of supporting users in managing their ‘qada fasting’ responsibilities. In conclusion, the Q’FAST mobile application provides a practical and accessible solution for tracking fasting obligations, improving record-keeping, and enhancing users’ awareness and consistency in fulfilling their religious duties.